Stress gradients and biodiversity: monoculture vulnerability drives stronger biodiversity effects during drought years - Wright, A.J.; Mommer, L.; Barry, K.; vanRuijven, J. (Ecology (Durham))
Climate change will increase the likelihood and severity of droughts into the future. Although diversity may buffer plant communities against the negative effects of drought, the mechanisms underlying this pattern remain unclear. Higher-diversity plant communities may have a higher likelihood of including more drought-resistant species that can compensate for drought-sensitive species (“insurance effects”). Alternatively, higher-diversity communities may alter environmental conditions and improve performance of even droughtsensitive species. Here we planted nonleguminous forbs and grasses into monocultures and four- and eight-species mixtures, and measured species and plot productivity every year from 2000 to 2010. We found that six of our eight species were suppressed when growing in monoculture during dry years. These same species were unaffected by drought when growing in higher-diversity mixtures. Because of this poor performance in monoculture (not insurance effects), the biodiversity productivity relationship was strongest during the driest years. If biodiversity ameliorates hot/dry conditions and therefore improves performance of drought-sensitive species during periods of low rainfall, this may mean biodiversity can be used as a tool to protect individual species from drought conditions.